К вопросу об особенностях политической модернизации в Турецкой Республике (1920-1930-е гг.) - Багдасарян, Сурен («Զանգակ - 97»)
In the Kemalist Turkey of 1920-1930s the modernization was laid in the basis of the national development being a matter of life and death. The goals of the modernization consisted in the strengthening of the State independence and the stable socio-political development. Process of the Turkish modernization has proeeeded complexly including the military, economic, scientific, social, and political spheres of life.
Keywords: История; Политика; Турция